Leisure Time Habits and Physical Activity Levels in Junior High School Students in the Kepulauan Seribu, Jakarta - Ganeswara, Raisa; Resmana, Dadan; Sutiyono, Bambang; Kridasuwarso, Bambang; Rihatno, Taufik; Samsudin, Samsudin; Ginanjar, Shela (Institut Teknologi Bandung, 2025)
Physical activity during adolescence plays a vital role in supporting optimal physical and mental development. This study aimed to assess physical activity levels and sedentary behavior among junior high school students in Thousand Islands regency of Jakarta, Indonesia. The research involved 215 students from grades VII and VIII, consisting of 104 males and 109 females. Physical activity levels were assessed using a modified version of the International Physical Activity Questionnaire (IPAQ) tailored for adolescents. The results indicated that the majority of students on both islands demonstrated moderate to high levels of physical activity, with a relatively low prevalence of sedentary behavior. These findings suggest that the students’ engagement in active routines is influenced by the geographic and socio-cultural characteristics of their island environment, which promote outdoor and communal activities. However, a small portion of students reported low activity levels, emphasizing the need for context-sensitive interventions to sustain and enhance active behaviors. This study highlights the importance of integrating localized health promotion strategies to prevent the long- term risks of obesity, metabolic disorders, and mental health challenges. The results serve as a valuable reference for health policymakers and educators in designing effective physical activity programs for youth in remote and coastal communities. Keywords: children, jakarta, leisure, physical activity, sedentary